2007
DOI: 10.1016/j.ymeth.2006.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Homebuilt single-molecule scanning confocal fluorescence microscope studies of single DNA/protein interactions

Abstract: Many technical improvements in fluorescence microscopy over the years have focused on decreasing background and increasing the signal to noise ratio (SNR). The scanning confocal fluorescence microscope (SCFM) represented a major improvement in these efforts. The SCFM acquires signal from a thin layer of a thick sample, rejecting light whose origin is not in the focal plane thereby dramatically decreasing the background signal. A second major innovation was the advent of high quantum-yield, low noise, single-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…In recent years, progress has been made in applying new technologies that have the potential to bridge the gap between static ultrastructural features and dynamic physiological processes in the study of chromatin. These technologies, which include scanning confocal fluorescence microscopy [ 2 ], molecular tweezers [ 3 , 4 ] and atomic force microscopy (AFM) [ 5 , 6 ], have provided remarkable insights into the behavior of individual nucleosomes. The combination of single-molecule resolution, solution biochemistry and observation of native macromolecular complexes has made AFM especially attractive for studying nucleosomes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, progress has been made in applying new technologies that have the potential to bridge the gap between static ultrastructural features and dynamic physiological processes in the study of chromatin. These technologies, which include scanning confocal fluorescence microscopy [ 2 ], molecular tweezers [ 3 , 4 ] and atomic force microscopy (AFM) [ 5 , 6 ], have provided remarkable insights into the behavior of individual nucleosomes. The combination of single-molecule resolution, solution biochemistry and observation of native macromolecular complexes has made AFM especially attractive for studying nucleosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have looked at the actual structures of Holliday junctions with various techniques, most commonly with microscopy and X-ray crystallography. For example, rather long sequences of cis−trans isomers have been observed by transmission electron microscopy (TEM), in recombination intermediatesand as predesigned sequences for protein interactions. , Scanning confocal fluorescence microscopy has been used on a small junction but for dynamic measurements only. The results have shown that in TEM studies the majority of the DNAs may have altered structures due to the mounting procedure; even when experimental conditions favoring, for example, the closed form (resulting in a ∼40° interduplex crystallographic angle) were chosen, in reality a variety of structures (open cross, Y-shape, k-shape, straight rod) were observed.…”
mentioning
confidence: 99%
“…sp-FRET has been realized with various techniques, for example, confocal microscopy detecting diffusing molecules in bulk solution, [2][3][4] imaging under the total internal reflection configuration, 5,6 and imaging by using confocal microscopy with sample scanning. 7 The sp-FRET technique has been widening its applicability in the field of single molecule spectroscopy for biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Because the FRET efficiency strongly depends on the donor−acceptor distance in a range comparable to the dynamics of biomolecules and can be optically measured, single-pair FRET (sp-FRET) measurements enable the investigation of molecular dynamics at a single molecule level. sp-FRET has been realized with various techniques, for example, confocal microscopy detecting diffusing molecules in bulk solution, imaging under the total internal reflection configuration, , and imaging by using confocal microscopy with sample scanning . The sp-FRET technique has been widening its applicability in the field of single molecule spectroscopy for biomolecules.…”
Section: Introductionmentioning
confidence: 99%